Automated White Pepper Bottle Filling Machine - Rahmarturllah, Mohd Asri (Progress in Engineering Application and Technology, 2021)
White and black pepper production in Sarawak state keep increasing since 2009. In Malaysia, Sarawak are the main production of pepper. Based on observation at Kampung Telok Melano, 90% out of 84 houses are pepper farmer. Pepper production is a main source of income for the community. Farmers at the Kampung Teluk Melano, still processing the pepper in manual method which is from raw until the output product. In order to increase the rate of pepper powder production, the farmer need an automated machine that are affordable. The aim of this project is to design bottle powder filling system layout. For system control of the machine, control system for the powder filling mechanism using PLC need to be develop. Verify the performance of the part and machine. Before fabrication process of the machine, all of the part is design in Solidwork in order to get the correct dimension. To select the suitable design layout for the machine, Pugh Metrix method is applied. For fabrication of the machine, the part is made by using 3D printer, stainless steel, zinc and aluminum. The auger dispenser is custom made. All of the part that involve in rotation movement are been analysis by using simulation. From the finding, by referring the CAD design, the machine is able to fabricate. It was found that all of the part that involved in rotation movement able to rotate as desired. By any means, in order to verify the machine production performance, test run which involving the PLC LLD program are needed.